ANALYSIS OF CHARACTER EDUCATION VALUES IN THE FILM JELITA SEJUBA BY RAY NAYOAN: Analisis Nilai-Nilai Pendidikan Karakter Dalam Film Jelita Sejuba Karya Ray Nayoan - Arfi Zukri; Dody Irawan; Zaitun; Ahada Wahyusari; Abdul Malik; Tessa Dwi Leoni (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research discusses the values of character education in the film "Jelita Sejuba" by Ray Nayoan. According to Endraswara (2011), literary works are a unique and organic phenomenon, full of meaning and function which are often blurred, because they require imagination. Literature is also considered a work of art that is born from the author's contemplation of reality, and contains important aesthetic elements. Film as a communication medium also contains character values such as moral, social, religious and political, highlighting Natuna coastal culture with an interesting story background, reflecting the life of the local community. The research method used is descriptive qualitative. This research found fifteen values of character education. It is hoped that this research can broaden students' insight into the value of character education in the film "Jelita Sejuba"